Pengaruh Citra Merek Terhadap Niat Beli pada Coffee Shop Dimediasi oleh Kepercayaan Merek - Ridho Arrafi; Harmanda Berima Putra (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of brand image on purchase intention through brand trust in Coffee Shop. This research employs a quantitative approach with a sample of coffee lovers who intend to repurchase coffee shop products. By collecting primary data through the distribution of questionnaires to 165 respondents. Data processing uses PLS-SEM software. The analysis results show that brand image has a positive effect on brand trust. Brand trust has a positive effect on repurchase intention and brand image has a positive effect on repurchase intention through brand trust.